Methodology to evaluate fatigue damage under multiaxial random loading. (November 2017) - Portugal, Ibai; Olave, Mireia; Zurutuza, Aitor; López, Arkaitz; Muñiz-Calvente, Miguel; Fernández-Canteli, Alfonso
Highlights: A methodology is necessary to estimate multiaxial fatigue damage in components. Manufacturers of products with similar behaviours will find the methodology useful. The stresses are complex and cannot be evaluated with von Mises or Tresca models. The stresses' non-proportionality obliges to apply a novel cycle counting system. Abstract: Manufacturers must assure the reliability of their products, what implies guaranteeing optimal working conditions during their service life. In this work, a methodology is proposed to estimate the damage experienced by a component under non-proportional loading to be made aiming at predicting when the component will fail and where the failure location will happen. In the present case, a novel cyclic counting model is introduced based on a hybrid variant of the rainflow algorithm applied to the results of the Papadopoulos critical plane approach using the Basquin fatigue model. In this way, the damage model is achieved.